2021
DOI: 10.1126/sciadv.abf6834
|View full text |Cite
|
Sign up to set email alerts
|

Differential recognition of oligomannose isomers by glycan-binding proteins involved in innate and adaptive immunity

Abstract: The recognition of oligomannose-type glycans in innate and adaptive immunity is elusive due to multiple closely related isomeric glycan structures. To explore the functions of oligomannoses, we developed a multifaceted approach combining mass spectrometry assignments of oligomannose substructures and the development of a comprehensive oligomannose microarray. This defined microarray encompasses both linear and branched glycans, varying in linkages, branching patterns, and phosphorylation status. With this reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
(101 reference statements)
3
18
0
Order By: Relevance
“…We found that Manα1,2Manα1,3Man and GlcNAcβ1,2Manα1,3Man bound with DC-SIGN were more stable than Manα1,2Manα1,2Man based on residence time. The findings were consistent with those from a recent glycan assay study ( Figure 6 C) [ 51 ]. We inferred that DC-SIGN recognizes glycan epitop50es when glycoforms expose them in a particular conformation.…”
Section: Resultssupporting
confidence: 92%
“…We found that Manα1,2Manα1,3Man and GlcNAcβ1,2Manα1,3Man bound with DC-SIGN were more stable than Manα1,2Manα1,2Man based on residence time. The findings were consistent with those from a recent glycan assay study ( Figure 6 C) [ 51 ]. We inferred that DC-SIGN recognizes glycan epitop50es when glycoforms expose them in a particular conformation.…”
Section: Resultssupporting
confidence: 92%
“…First, we used the recently published oligomannose array for this purpose. [ 53 ] Here, investigators assayed a variety of subtly different oligomannose glycans for their binding to various lectins. The slight changes in glycan structure, which nonetheless led to appreciable differences in their binding behavior, made this a particularly challenging case study for our model.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting the cell surface expression of oligomannose, several mannose-recognizing receptors such as macrophage mannose receptor (CD206), DC-SIGN [ 79 ], langerin [ 80 ] and dectin-2 [ 81 ] have been found to recognize oligomannosidic N -glycans expressed on tumour cells [ 82 ]. The recent development of a comprehensive oligomannose microarray may open for the identification of additional receptors recognizing oligomannose-decorated cancer cells and tissues [ 83 ].…”
Section: Resultsmentioning
confidence: 99%